Enhancement of algae ponds for rural domestic sewage treatment by prolonging daylight using artificial lamps - Yuxuan Mao (Elsevier, 2021)
Algal ponds (APs) are widely used as treatment facilities for domestic sewage in sparsely populated rural areas. However, few AP studies have focused on daylight length to enhance pollutants removal. In this study, four algae ponds were set up, daylight was prolonged by 0, 2, 4, and 6 h with an illuminating intensity of 3000 lx. The highest removal efficiencies of total nitrogen, ammonium, and total phosphorus were 37.36%, 41.20%, and 21.56% due to the highest microbial abundance under optimum conditions (2 h PD), respectively. Excessive PD (4 h and 6 h) could inhibit the removal abilities. PD also increased the maximum relative electron transport rate of algae, leading to an increase in the photosynthetic capacity of APs. Meanwhile, the high microbial abundance indicates that chemoheterotrophic bacteria are the main influencing factor for the removal of nitrogen and phosphorus by the APs. Moreover, the system with PD using artificial lamps was proven to be feasible for engineering applications and potentially utilized in rural domestic wastewater treatment.